(untitled) (Mustansiria Dental Journal, 2004)
Abstract: One of the problems in Orthodontics and Oral Surgery si determining when to extract third molars or when it is advisable to let them complete their eruption. This study attempts to establisha computerized prediction method using lateral cephalometric radiographs to decide whether removal or leaving third molars to erupt. The result showed that there is a significant difference in the accuracy of manual and computerized method of prediction of lower third molar eruption ni that the computerized method proved to be more accurate ni the prediction.